Expressão de reguladores de ubiquitinação e sumoilação durante o desenvolvimento embrionário e em resposta a lesões no DNA - Silva, Zigomar da (2022)
Normal embryo development depends on the correct occurrence of several events, including chromatin remodeling, embryo genome activation, cell differentiation, as well as the maintenance of genomic integrity. Both endogenous and exogenous factors can cause DNA damages in embryos, being DNA double-strand breaks (DSBs) the most deleterious for embryo development. For DSB repair, embryos preferentially activate the homologous recombination (HR) pathway. All cellular and molecular events that coordinate development must occur at an adequate time and intensity, which depends on many factors and complex regulatory mechanisms. Ubiquitination and sumoylation are post-translational modifications of proteins by ubiquitin and SUMOs (Small Ubiquitin-related Motifs) proteins. Ubiquitination and sumoylation are coordinated by cascade reactions of ubiquitin-activating (E1), ubiquitin-conjugating (E2), and ubiquitin-binding enzymes (E3) or ubiquitin ligases (UBs)/SUMO ligases (SUMOs). Ubiquitination and sumoylation are reversed by deubiquitination and desumoylation, respectively. Removal of ubiquitin and SUMO from proteins is performed by deubiquitinases (DUBs) and sumoilases (deSUMOs), respectively. Ubiquitination and sumoylation play important roles in the regulation of proteins, and consequently, cellular processes, such as the regulation of proteolysis, protein quality control, nuclear localization, chromatin structure, chromosome condensation, gene expression, DNA replication and repair, and modulation of signaling pathways. Ubiquitination and sumoylation are involved in the regulation of embryo development, however, their specific effects and importance in different species, including swine, are poorly understood. Thus, the present thesis aimed to: i) determine the expression patter of UBs, DUBs, SUMOs and deSUMOs during in vitro development of porcine embryos; ii) evaluate the impact of induced DNA damages on the expression of UBs, DUBs, SUMOs and deSUMOs in porcine embryos at different stages of development; and ii) investigate the role of the E3s DAC13 and RNF1114 on development of porcine embryos. Transcript levels of most UBs, DUBs, SUMOs, and deSUMOs evaluated in this study were higher in oocytes and early-stage embryos than in blastocysts. Transcript levels for UBs (RNF20, RNF40, RNF114, RNF169, CUL5, DCAF2, DECAF13 and DDB1), DUBs (USP16) and SUMOs (CBX4, UBA2 and UBC9) were transiently upregulated in early-stage embryos (D2 and/ or D4) compared to oocytes and blastocysts, indicating a possible role in the EGA in this species. UVinduced DNA damage altered the mRNA abundance of several UBs, DUBs, SUMOs and deSUMOs enzymes on D2 (RNF4, RNF8, RNF20, RNF114, RNF126, RNF168, DCAF2, DDB1, UBE2N, USP7, USP11, USP16, USP34, OTUB1, OTUB32, BAP1, PIAS1, PIAS2, PIAS4, CBX4, UBC9 and SENP2), D4 (RNF8, RNF126, RNF168, BRCC3, UBE2N, USP7, USP16, BAP1, PIAS1, CBX4, UBA2 and SENP2) and D7 (RNF40, RNF168, BRCC3, CUL5, DCAF13, DDB1, UBE2N, USP11, USP34, PIAS2, CBX4, UBA2 and UBC9). In the early stages of embryo development (D2 and D4), the transcript levels of several UBs, DUBs, SUMOs and deSUMOs enzymes were decreased in response to DNA damage, which suggests they were of maternal origin and were translated in response to the induced damage. Our studies revealed that normal development of swine embryos depends on the normal expression of E3s DCAF13 and RNF114. Our findings also provide evidence that DCAF13 and RNF114 coordinate embryo development by modulating the expression of epigenetic modifiers involved in the regulation of chromatin functions and DNA repair.